MICROPLASTIC FIBER ACCUMULATION IN SOME WILD AND CULTURED SHRIMP SPECIES - Van Chi Vo; Thi Bich Hang Tran (Tạp chí Khoa học Đại học Đà Lạt)
This study was conducted to examine the microplastic fiber abundance and its characteristics in two wild and two cultured shrimp species collected at coastal areas in Hoai Nhon district, Binh Dinh Province. A total of 84 individuals of four shrimp species, Litopenaeus vannamei, Penaeus monodon, Metapenaeus ensis, and Penaeus semisulcatus were collected for analysis. All shrimp specimens were dissected to remove the digestive tracts, which were then treated with 10% KOH to collect microplastic fibers by filtering. The microplastic fiber concentrations varied from 1.96 ± 0.09 to 19.33 ± 10.82 fibers/specimen or 0.20 ± 0.12 to 2.26 ± 1.26 fibers/g of wet body weight. The abundance of fibers in the wild shrimps (Penaeus semisulcatus and Metapenaeus ensis) was higher than in the cultured shrimps (Penaeus monodon and Litopenaeus vannamei). Most fibers observed in the four shrimp species had lengths between 300 and 1500 μm, accounting for 78.72% to 92.82% of the total). White fibers were dominant (30.38%), followed by gray (11.87%), and green (10.60%).